PENGARUH METODE MULTISENSORI TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 DI SDIT LUHUR AL-KAUTSAR - Nurmalinda, Egin; Susilawati , Susilawati; Labudasari , Erna (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to determine the initial reading ability of class I students at SDIT Luhur Al-Kautsar before and after implementing the multisensory method, as well as to determine the effect of the multisensory method on initial reading ability. The research method used was pre-experiment with a one group pretest-posttest design. The research subjects consisted of 21 students, and data was collected through oral tests. The results of the descriptive analysis show that the pretest scores show the following data: the number of students (N) is 21; minimum score is 0; maximum score is 10; total score reached 94; average score of 4.48; and standard deviation 3.386. The average pretest score was 8.24 with a standard deviation of 3.386 after applying the multisensory method. The normality test using the One-Sample Kolmogorov-Smirnov Test showed that the data was normally distributed (p = 0.000). Hypothesis testing with the t test (Paired Sample T-test) found a significant difference between posttest and pretest scores (Z = 0.117, p = 0.000), indicating that the use of multisensory methods has a positive effect in improving student learning outcomes. The difference in increase in the average score of 3.76 (from 4.48 on the pretest to 8.24 on the posttest) shows a significant increase in student learning outcomes. The conclusion of this research shows that the multisensory method had an influence in improving students' initial reading abilities. These findings suggest that the use of multisensory methods can be applied as an effective learning strategy to improve reading skills in elementary schools.